2006
DOI: 10.1111/j.1540-4781.2006.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Reading the Research Make a Difference? A Case Study of Teacher Growth in FL German

Abstract: Although the research literature on Second Language Acquisition (SLA) has increased exponentially over the last few decades, it is not at all clear how its findings may or may not contribute to teacher growth or otherwise influence actual classroom praxis. The case study presented here shows one instructor, a native speaker of German, translating theory into practice in a beginning German as a foreign language college classroom. The theory employed in this case concerns corrective feedback in oral production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…In contrast, other studies have shown that teacher education had a large impact (Angelova 2005;Busch 2010;Kettle and Sellars 1996;MacDonald, Badger, and White 2001;Murray 2003). Such variation results, in part, because knowledge of teaching is not simply transmitted to, followed, or realized by prospective teachers; rather such knowledge is informed by prior experiences and beliefs (Freeman 1993(Freeman , 1996Johnson and Golombek 2002;Rankin and Becker 2006). In addition, Borg (2011) suggests that although a change in stated beliefs may not occur as a result of teacher training, a better ability to articulate one's beliefs is also a possible and important outcome.…”
Section: L2 Teachers' Stated Beliefsmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, other studies have shown that teacher education had a large impact (Angelova 2005;Busch 2010;Kettle and Sellars 1996;MacDonald, Badger, and White 2001;Murray 2003). Such variation results, in part, because knowledge of teaching is not simply transmitted to, followed, or realized by prospective teachers; rather such knowledge is informed by prior experiences and beliefs (Freeman 1993(Freeman , 1996Johnson and Golombek 2002;Rankin and Becker 2006). In addition, Borg (2011) suggests that although a change in stated beliefs may not occur as a result of teacher training, a better ability to articulate one's beliefs is also a possible and important outcome.…”
Section: L2 Teachers' Stated Beliefsmentioning
confidence: 88%
“…Kamiya and S. Loewen and it is clear that John had a lot to say about Truscott's pedagogical claims, and many of his comments were framed in terms of his own classroom experiences. Although the articles did not appear to influence the nature of John's stated beliefs, they did succeed in raising John's awareness of his CF practices; such awareness raising has been argued to be a significant benefit of reading research studies for L2 teachers (Ellis 1997;Mackey, Polio, and McDonough 2004;Rankin and Becker 2006). As an experienced teacher, John admitted that he had not thought much about CF recently and that any CF in the classroom occurred 'naturally' and 'automatically.'…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Although a variety of practice‐related variables are intertwined in the classroom, understanding how each variable and its combination influence L2 learning processes provides a strong theoretical backbone for teachers to think and act upon. The empirical findings may prompt L2 teachers to reflect on their classroom teaching such as design of materials, intervals of repeated practice, and individual differences of learners (Rankin & Becker, ), as well as provide emotional support for their teaching (Sato & Loewen, ).…”
mentioning
confidence: 99%
“…However, research studies that have considered how graduate students develop the first three professional and pedagogical components have been quite limited in number and scope. Interestingly, many of the published empirical studies that were cited by Allen and Negueruela‐Azarola () focused on, or were the product of, German departments (e.g., Gonglewski & Penningroth, ; Huffman, ; Rankin & Becker, ). Ryan‐Scheutz and Rustia () collected data about 290 TAs who were employed by Italian programs in North America in order to determine how these TAs were being prepared to teach, their background, and who prepared them for teaching.…”
Section: Literature Reviewmentioning
confidence: 99%